Development of a simulated lung fluid leaching method to assess the release of potentially toxic elements from volcanic ash. (September 2021) - Tomašek, Ines; Damby, David E.; Stewart, Carol; Horwell, Claire J.; Plumlee, Geoff; Ottley, Christopher J.; Delmelle, Pierre; Morman, Suzette; El Yazidi, Sofian; Claeys, Philippe; Kervyn, Matthieu; Elskens, Marc; et al.
Abstract: Freshly erupted volcanic ash contains a range of soluble elements, some of which can generate harmful effects in living cells and are considered potentially toxic elements (PTEs). This work investigates the leaching dynamics of ash-associated PTEs in order to optimize a method for volcanic ash respiratory hazard assessment. Using three pristine (unaffected by precipitation) ash samples, we quantify the release of PTEs (Al, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, V, Zn) and major cations typical of ash leachates (Mg, Na, Ca, K) in multiple simulated lung fluid (SLF) preparations and under varying experimental parameters (contact time and solid to liquid ratio). Data are compared to a standard water leach (WL) to ascertain whether the WL can be used as a simple proxy for SLF leaching. The main findings are: PTE concentrations reach steady-state dissolution by 24 h, and a relatively short contact time (10 min) approximates maximum dissolution; PTE dissolution is comparatively stable at low solid to liquid ratios (1:100 to 1:1000); inclusion of commonly used macromolecules has element-specific effects, and addition of a lung surfactant has little impact on extraction efficiency. These observations indicate that a WL can be used to approximate lung bioaccessible PTEs in an eruption response situation. This is a useful step towards standardizing in vitro methods to determine the soluble-element hazard from inhaled ash. Graphical abstract: Image 1 Highlights: Investigation of a lung fluid leachate method to assess inhalation hazards of ash. Element release in leachates is both method-parameter and sample dependent. Inclusion of lung surfactant is not necessary when assessing ash leachates. Optimal method parameters are extraction up to 24 h at 1:100 ratio. Water leach can be used as a conservative estimate of lung bioaccessible elements.